2015
DOI: 10.1016/j.landusepol.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Does the Green Great Wall effectively decrease dust storm intensity in China? A study based on NOAA NDVI and weather station data

Abstract: a b s t r a c tChina launched its "Green Great Wall" (GGW) program in 1978. However, the effects of this program are subject to intense debate. This study compares changes in the vegetation index in regions where the GGW program has been implemented with those where it has not. Subsequently, a definition to measure dust storm intensity (DSI) was proposed that better calculates the intensity of dust events; it considers the frequency, visibility, and duration of dust events. The results show that in the GGW reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…The GGW program has greatly improved vegetation cover and effectively reduced dust storm intensity in parts of northern China [8], but other researchers point to warmer temperatures and greater rainfall as being more important drivers of greening trends in the area [146], and the value of large-scale afforestation in controlling desertification and soil erosion in China has been questioned due to low tree survival rates [147]. Huang et al [148] report that rangeland restoration programs have resulted in a systematic increase in the area of grassland in most northern and western regions, but Su et al [149] warn that bush encroachment is an unexpected outcome of the grazing ban on sandy rangelands in Inner Mongolia.…”
Section: Contemporary National Regional and International Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…The GGW program has greatly improved vegetation cover and effectively reduced dust storm intensity in parts of northern China [8], but other researchers point to warmer temperatures and greater rainfall as being more important drivers of greening trends in the area [146], and the value of large-scale afforestation in controlling desertification and soil erosion in China has been questioned due to low tree survival rates [147]. Huang et al [148] report that rangeland restoration programs have resulted in a systematic increase in the area of grassland in most northern and western regions, but Su et al [149] warn that bush encroachment is an unexpected outcome of the grazing ban on sandy rangelands in Inner Mongolia.…”
Section: Contemporary National Regional and International Plansmentioning
confidence: 99%
“…Attempts to combat wind erosion with soil conservation measures have succeeded in reducing SDS in certain parts of the world (e.g., [7,8]) but in other areas there has been a recent marked increase in wind erosion and associated dust storms. These areas include parts of the Arabian Peninsula [9,10], the eastern Mediterranean [11,12], Lower Mesopotamia and adjacent regions [13], and parts of northeast Asia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the Three-North Forest Shelterbelt Program is performing well in combating desertification and SDS events is still debatable, but countermeasures should be adopted in this region [65,66]. The map of the major transportation routes of sand and dust storms, combined with the results of SDSI, could help the government and policy makers more accurately and effectively address SDS issues.…”
Section: Major Transportation Routes Of Sand and Dust Storms In The Tmentioning
confidence: 99%
“…It has made great achievements since its initiation in 1978 and will continue for 75 years until 2050 [39]. Many research and assessment efforts linked to the TNSFP have focused on vegetation dynamics, and previous studies has reported that vegetation have greatly improved in the TNSFP region, while it varied dramatically outside the TNSFP region during 1981-1998 [40], indicating a positive effect of the TNSFP on vegetation growth. Meanwhile, regional study results also showed a substantial forest increase in Yulin district from 1974 to 2010 [41].…”
Section: Role Of Ecological Restoration In Vegetation Dynamicsmentioning
confidence: 99%